The Effect of Access to Suitable Drinking Water, Health Budget, Health Facilities, Poor Population, Average Years of Schooling, Smoking Prevalence, And Health Human Resources on Life Expectancy in Indonesia 2015-2024 - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
Life expectancy (LE) represents a core dimension of human development and is a strategic benchmark for realizing Indonesia’s Golden Vision 2045, which aims to raise the national average to over 80 years. Yet, progress toward this goal continues to face obstacles such as inadequate access to clean water, disparities in the distribution of health facilities and personnel, persistent poverty, and high smoking prevalence. This research applies a quantitative design with provincial panel data to examine how several key factors—including safe drinking water access, public health spending, health infrastructure, poverty levels, average years of schooling, smoking prevalence, and health workforce availability—affect LE in Indonesia. The study seeks to identify the most influential determinants of longevity while offering policy-oriented insights. The results indicate that health infrastructure, education levels, and poverty rates are significant predictors of LE, whereas safe water access, health expenditure, smoking, and health workforce availability show limited statistical influence. These findings suggest that long-term investments in healthcare systems, education, and poverty reduction are vital to accelerate improvements in life expectancy and achieve the 2045 development agenda.